Engineered systems of inducible anti-repressors for the next generation of biological programming - Thomas M. Groseclose (Nature Portfolio, 2020)
Transcriptional anti-repressors have been largely absent in the design of regulated genetic circuits. Here, the authors present a workflow of the engineering of non-natural anti-reperssors that can be built into NOT oriented logic gates.